The Spinnability of PA6/CS-NPs Nanofiber Filaments via a One-step Multi-Needle Electrospinning Method with a Flowing Water Bath (Journal of Fiber Bioengineering and Informatics, 2020)
Wet electrospinning is a convenient and versatile method to produce nanofibers. When adding an activeagent into the bath solution, functional fibers may be fabricated in the fiber-forming process. In thispaper, the spinnability of PA6/CS-NPs hybrid nanofiber filaments was studied which might obtainantibacterial activity. Three dispersants were selected, including span-80 and tween-80 (ST) (1/1, w/w),sodium polyacrylate (PAAS) and methyl cellulose (MC) to improve the dispersibility of the chitosannanoparticles (CS-NPs) in the Peregal O aqueous solution. The mixture of ST was finally determined tobe applied in the bath solution mainly because the agglomeration of CS-NPs could be largely reducedand the suspension of CS-NPs be maintained comparatively stable, and the continuous spinning time waslonger than the others. When ST was added into the bath solution to fabricate the fibers, by varying thecompositions of the bath solution, including concentrations of the CS-NPs and ST, the morphologies ofPA6/CS-NPs fibers were investigated. When the composition of the bath solution was 0.2 wt.% ST and0.4 wt.% CS-NPs, the maximum number of CS-NPs could be observed on the surface of the nanofibers.Compared to the pure PA6 nanofiber filaments, the mechanical properties of the PA6/CS-NPs hybridnanofiber filaments would be weakened.